Negative feedback as a factor and source of particularity: From chaos theory to new trends in psychological research - Γ. Παπαδόπουλος, Νίκος; Σταμπουλίδης, Παύλος (Psychology: the Journal of the Hellenic Psychological Society, 2020)
ABSTRACT IS AVAILABLE IN THE PDF